048 Is it safe to discharge patients 24 h after uncomplicated successful primary percutaneous coronary intervention?. (16th May 2012) - Howard, J P; Jones, D A; Gallagher, S; Rathod, K; Jain, A; Mohiddin, S; Knight, C; Mathur, A; Smith, E J; Wragg, A
Abstract : Background: Primary percutaneous coronary intervention (PPCI) has led to improved mortality, reduced rates of recurrent ischaemia and shorter hospital stays compared to thrombolysis. Data from our centre published previously show that in low-risk patients very early discharge at 48 h is feasible and safe. We investigated whether in a group of low risk patients stratified to 48-h discharge, 24-h discharge would be potentially feasible. Methods: We undertook an observational study at an interventional cardiology centre involving 2980 patients who underwent Primary PCI from January 2004 to July 2011. Patients with TIMI 3 flow, ST segment resolution, good or moderate left ventricular function, and no dysrhythmia post-PPCI were discharged at 2 days. Remaining higher risk patients were discharged when judged clinically fit. All patients were offered outpatient review by a multidisciplinary team. Follow-up was collected for a median of 2.8 years (IQR 1.3–4.4 years). Results: Of the 2980 patients, 1174 (39.4%) were judged suitable for 48-h discharge. Of these, 964 patients (82.1%) were discharged at 48 h, with 210 discharged after longer inpatient stays. Of these 210 patients discharged after 2 days, 150 were delayed due to timing issues (admission at unsociable hours, eg, 01:00). 60 (5.1%) patients fitting criteria had their planned 48-h discharge delayed due to a clinical complication, of which 53 occurred within the first 24 h (including six MACE events and seven arrhythmias, there were no deaths) (Abstract 048 table 1 ). Only seven patients (0.60%) developed complications after 24 h, of which only 1 (0.09%) suffered a MACE event (target vessel revascularisation), with the remaining complications being abnormal blood tests (renal/liver function) or drug reactions (eg, rash). There were no in-hospital deaths in the 48-h group. Conclusion: Simple clinical criteria can be used to identify low-risk patients suitable for very early discharge 48 h following uncomplicated successful primary PPCI. With only a small percentage of complications occurring after the first 24 h, discharge after 24 h may be safe and warrants further study.